IMPLEMENTATION OF DISTRIBUTION OF NON-CASH FOOD ASSISTANCE THROUGH THE CASH GIRO POS APPLICATION - Andinie Sakila Putri; Dian Purwanti; Yana Fajar FY Basori (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Non-Cash Food Assistance (BPNT) is assistance to provide social protection to poor/poor vulnerable communities originating from the Ministry of Social Affairs of the Republic of Indonesia which will be given to the community based on Integrated Social Welfare Data (DTKS). In 2020 the Ministry of Social Affairs and PT Post are working together to speed up the distribution process using application of The Post Giro Cash (PGC). This study aims to find out how the implementation of application of The Post Giro Cash (PGC) in distributing Non-Cash Food Assistance (BPNT) at PT Post of Cisaat. This research method is a qualitative research method with a narrative approach. In determining the informants in this study using non-probability sampling technique snowball sampling. Data collection techniques include observation, interviews, documentation, audio-visual material. The results of this study indicate that the Implementation using of application of PGC in Distributing Non-Cash Food Assistance (BPNT) at PT Post of Cisaat has been running effectively, seen from the organization the formation of the bureaucratic structure has gone well, Interpretation or Interpretation has been fulfilled and Implementation has been carried out in accordance with the Standard Operating Procedures (SOP) in the regulations that have been set.